Studies on biological reduction of chromate by Streptomyces griseus - Poopal, Ashwini C.; Laxman, Ryali Seeta (Journal of Hazardous Materials, 2009)
Chromium is a toxic heavy metal used in various industries and leads to environmental pollution due to improper handling. The most toxic form of chromium Cr(VI) can be converted to less toxic Cr(III) by reduction. Among the actinomycetes tested for chromate reduction, thirteen strains reduced Cr(VI) to Cr(III), of which one strain of Streptomyces griseus (NCIM 2020) was most efficient showing complete reduction within 24h. The organism was able to use a number of carbon sources as electron donors. Sulphate, nitrate, chloride and carbonate had no effect on chromate reduction during growth while cations such as Cd, Ni, Co and Cu were inhibitory to varying degrees. Chromate reduction was associated with the bacterial cells and sonication was the best method of cell breakage to release the enzyme. The enzyme was constitutive and did not require presence of chromate during growth for expression of activity. Chromate reduction with cell free extract (CFE) was observed without added NADH. However, addition of NAD(P)H resulted in 2-3-fold increase in activity. Chromate reductase showed optimum activity at 28 degrees C and pH 7 (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Bioreduction; Chromate reductase; Hexavalent chromium; Streptomyces griseus